Cholinergic and Noradrenergic Modulation of Corticothalamic Synaptic Input From Layer 6 to the Posteromedial Thalamic Nucleus in the Rat - Nersisyan, Syune; Bekisz, Marek; Kublik, Ewa; Granseth, Björn; Wróbel, Andrzej (Frontiers in Neural Circuits, 2021)
Cholinergic and noradrenergic neuromodulation of the synaptic transmission from cortical layer 6 of the primary somatosensory cortex to neurons in the posteromedial thalamic nucleus (PoM) was studied using an in vitro slice preparation from young rats. Cholinergic agonist carbachol substantially decreased the amplitudes of consecutive excitatory postsynaptic potentials (EPSPs) evoked by a five-pulse train. The decreased amplitude effect was counteracted by a parallel increase of synaptic frequency-dependent facilitation. We found this modulation to be mediated by muscarinic acetylcholine receptors. In the presence of carbachol the amplitudes of the postsynaptic potentials showed a higher trial-to-trial coefficient of variation, which suggested a presynaptic site of action for the modulation. To substantiate this finding, we measured the failure rate of the excitatory postsynaptic currents in PoM cells evoked by "pseudominimal" stimulation of corticothalamic input. A higher failure-rate in the presence of carbachol indicated decreased probability of transmitter release at the synapse. Activation of the noradrenergic modulatory system that was mimicked by application of norepinephrine did not affect the amplitude of the first EPSP evoked in the five-pulse train, but later EPSPs were diminished. This indicated a decrease of the synaptic frequency-dependent facilitation. Treatment with noradrenergic α-2 agonist clonidine, α-1 agonist phenylephrine, or β-receptor agonist isoproterenol showed that the modulation may partly rely on α-2 adrenergic receptors. Coefficient of variation analysis did not suggest a presynaptic action of norepinephrine. We conclude that cholinergic and noradrenergic modulation act as different variable dynamic controls for the corticothalamic mechanism of the frequency-dependent facilitation in PoM.